2016
DOI: 10.1073/pnas.1613440113
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Long-term aggregation of larval fish siblings during dispersal along an open coast

Abstract: Center. In our study, we used microsatellite genotypes to infer that 57 of 491 new splitnose rockfish (Sebastes diploproa) recruits were siblings, suggesting cohesive dispersal over a 4-6 month period. After their examination of the raw data, Drs. Anderson and Garza suggested an alternative hypothesis in which the results derived from the existence of a cryptic species within our sample collection. We supplied them with all of the biological samples to reanalyze using a novel next-generation sequencing approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 69 publications
0
26
0
Order By: Relevance
“…Ours is the first study, to our knowledge, to explicitly address the presence of potentially confounding species in our analysis of larval dispersal, which, although not necessarily crucial for parentage assignment, is a minimum requirement for accurate sibship analysis. Although this analytical challenge may not affect some studies, the presence of marine species complexes in both tropical and temperate ecosystems deserves attention, as sibship analysis with a data set containing genotypes from two or more species that have been misidentified as a single species can lead to the spurious identification of visually indistinguishable, but nontarget, conspecifics as siblings (Ottmann et al, ). Choosing a genetic marker set with the capacity to differentiate species allowed us to include samples from juvenile fish that were not morphologically identified in the field, as well as to definitively identify the samples that were misidentified or mislabelled during field sampling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ours is the first study, to our knowledge, to explicitly address the presence of potentially confounding species in our analysis of larval dispersal, which, although not necessarily crucial for parentage assignment, is a minimum requirement for accurate sibship analysis. Although this analytical challenge may not affect some studies, the presence of marine species complexes in both tropical and temperate ecosystems deserves attention, as sibship analysis with a data set containing genotypes from two or more species that have been misidentified as a single species can lead to the spurious identification of visually indistinguishable, but nontarget, conspecifics as siblings (Ottmann et al, ). Choosing a genetic marker set with the capacity to differentiate species allowed us to include samples from juvenile fish that were not morphologically identified in the field, as well as to definitively identify the samples that were misidentified or mislabelled during field sampling.…”
Section: Discussionmentioning
confidence: 99%
“…While the identification of parent–offspring relationships has been the dominant form of relationship inference used in the study of dispersal in the marine realm, Schunter, Pascual, Garza, Raventos, and Macpherson () showed how combining identification of sibling groups with parentage analysis provides a more complete description of dispersal patterns. Such sibship analysis has since seen additional use in the study of marine fishes (e.g., Ottmann et al, ), but Baetscher, Clemento, Ng, Anderson, and Garza () have shown that most such analyses have lacked sufficient power to accurately identify sibling groups.…”
Section: Introductionmentioning
confidence: 99%
“…Other mechanisms, such as the gregarious settlement of the larvae of many sedentary marine animals, including some cnidarians, barnacles, polychaete worms, ascidians, gastropods, bivalves, sipunculid and echiuran worms, echinoderms and urochordates, or aggregation of adults during spawning, promote the establishment of locally large and dense populations or high densities of gametes (Knight-Jones 1953;Burke 1986;Levitan 1988;Levitan 2002;Young 1990;Pawlik 1992). Likewise, interactions between larval behaviours and physical transport processes can lead to coherent larval dispersal, and perhaps aggregated settlement (Siegel et al 2008;Katija & Dabiri 2009;Iacchei et al 2013;Ottmann et al 2016). Aggregation for mating or dispersal can, however, subject a population to local catastrophes if the latter happen to coincide with critical sites or times of breeding, fuel the transmission of disease (Lafferty & Holt 2003), increase the risk of polyspermy in broadcast spawning invertebrates (Levitan 2002, Levitan 2012SerrĂŁo & Havenhand 2009), and promote other forms of reproductive failure (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Granted Shanks and Eckert (2005) were referring to parental populations at a very coarse scale (e.g., northern and southern CCS), evidence of IBD and relatedness within several sites suggests that local recruitment may occur to some degree on a smaller scale. It is less likely that the relatedness found in this study is driven by sweepstakes reproductive success, which is typically followed by chaotic genetic patchiness or otherwise unpatterned population genetic structure not observed here (Christie et al, 2010;Hedgecock & Pudovkin, 2011 Ottman et al, 2016). Future studies could assess demographic processes of larvae (e.g., larval dispersal trajectory, mortality rate, interaction with fine-scale oceanographic conditions), as well as genetic variation within and among settlement cohorts to better understand how early life-history characteristics contribute to possible kin aggregation of Dungeness crab in the CCS.…”
Section: Evidence For Strong Connectivity and Geographically Limitementioning
confidence: 72%
“…Lastly, it is possible that cohesive dispersal of kin throughout the planktonic larval phase could result in relatedness in the adult population, although this would be somewhat remarkable, given that Dungeness crab larvae leave the continental shelf and return inshore over a roughly four month period. Turbulence from wind and swell would likely diffuse kin; however, this behaviour has been hypothesized with compelling evidence in other species having lengthy PLDs (kelp bass P. clathratus , Selkoe et al., ; Miry's demoiselle Neopomacentrus miryae , Ben‐Tzvi et al., ; domino damselfish Dascyllus trimaculatus , Bernardi, Beldade, Holbrook, & Schmitt, ; California spiny lobster P. interruptus , Iacchei et al., ; splitnose rockfish Sebastes diploproa , Ottman et al., ). Future studies could assess demographic processes of larvae (e.g., larval dispersal trajectory, mortality rate, interaction with fine‐scale oceanographic conditions), as well as genetic variation within and among settlement cohorts to better understand how early life‐history characteristics contribute to possible kin aggregation of Dungeness crab in the CCS.…”
Section: Discussionmentioning
confidence: 99%